Hemorrhagic Stroke Induces a Time-Dependent Upregulation of miR-150-5p and miR-181b-5p in the Bloodstream - Cepparulo, Pasquale; Cuomo, Ornella; Vinciguerra, Antonio; Torelli, Monica; Annunziato, Lucio; Pignataro, Giuseppe (Frontiers in Neurology, 2021)
To date, the only effective pharmacological treatment for ischemic stroke is limited to the clinical use of recombinant tissue plasminogen activator. Unfortunately, the benefit of this treatment is limited to a 4.5 hours time window. Most importantly, the use of rt-PA is contraindicated in the case of haemorrhagic stroke. MicroRNAs (miRNAs)are stable non-coding RNA crucially involved in the downregulation of gene expression via mRNA cleavage or translational repression. In the present paper, taking advantage of three preclinical animal models of stroke, we compared miRNA blood levels of animals subjected to permanent or transient Middle Cerebral Artery occlusion (MCAO),or to collagenase-induced hemorrhagic stroke. Preliminarily, we examined the miRnoma, 548 miRNAs, in brain tissue of ischemic and sham operated rats, then we selected those miRNAs whose expression was significantly modulated after stroke, to create a list of miRNAs potentially involved in stroke damage. These selected miRNAs have been then evaluated at different time intervals in the blood of rats subjected to permanent or transient focal ischemia, or to hemorrhagic stroke. From a first skimming that allowed us to select 15 circulating miRNAs, we found that 4 miRNAs, miR-16-5p,miR-101a-3p,miR-218-5p and miR-27b-3p,were significantly upregulated in plasma of rats three hours after permanent MCAO, whereas other four different miRNAs, miR-150-5p,let-7b-5p,let 7c-5p and miR-181b-5p,were selectively upregulated by collagenase-induced hemorrhagic stroke. Collectively, our study identified some selective miRNAs expressed in the plasma of hemorrhagic rats and pointed out the importance of a precise time point measurement to render more reliable the use of miRNAs as stroke biomarkers.